2019
DOI: 10.1080/14760584.2019.1562907
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing uptake of influenza maternal vaccine

Abstract: Introduction: Influenza vaccination during pregnancy can offer many benefits to both mother and infant. Despite recommendations from the Advisory Committee on Immunization Practices, vaccine coverage rates among pregnant women during pregnancy are below 40% in the United States. There is a need for a greater understanding of what interventions can improve vaccine uptake among pregnant women. Areas covered: This review synthesizes the existing evidence on the effectiveness of interventions to improve maternal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 79 publications
2
55
0
Order By: Relevance
“…However, our study has demonstrated that factors specific to the vaccine, perhaps more so than the disease are highly influential. Interventions recommended to improve maternal vaccination uptake have ranged from text reminders for prospective mothers to educational videos and motivational interviewing techniques for HCPs [110][111][112]. Based on the results of this review, interventions designed to impact maternal vaccine uptake should continue to encourage individualised HCP recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study has demonstrated that factors specific to the vaccine, perhaps more so than the disease are highly influential. Interventions recommended to improve maternal vaccination uptake have ranged from text reminders for prospective mothers to educational videos and motivational interviewing techniques for HCPs [110][111][112]. Based on the results of this review, interventions designed to impact maternal vaccine uptake should continue to encourage individualised HCP recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in a research study [ 33 ] such as the present one, after a specific training program for midwives, the probabilities of the women who received the flu vaccine during pregnancy were significantly greater after the implementation of the program. The midwives were able to establish a relationship of trust, availability, and support during the decision-making process of the pregnant women related their health and that of their future child, and also performed promotion and mother—child education activities as part of their habitual activities [ 34 , 35 , 36 ] On the other hand, the midwives asked for more time, resources and continuous training [ 37 , 38 , 39 ]. The recommendation of the professional health worker, having the vaccine available and free in the consultation itself, were favorable factors as observed in our study [ 28 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccinating pregnant women is generally regarded as safe [159][160][161][162][163][164][165]. However, some hesitancy over influenza vaccination is present in this population and the benefit of protecting both the mother and the fetus needs to be conveyed as outweighing the risk of potential side effects [223][224][225][226].…”
Section: Increasing Vaccination Rates For Influenzamentioning
confidence: 99%